2020
DOI: 10.3390/cancers12082129
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Heterogeneity of Cutaneous T-Cell Lymphomas Revealed Using RNA-Seq Technologies

Abstract: Cutaneous T-cell lymphomas (CTCLs) represent a large, heterogeneous group of non-Hodgkin lymphomas that primarily affect the skin. Among multiple CTCL variants, the most prevalent types are mycosis fungoides (MF) and Sézary syndrome (SS). In the past decade, the molecular genetics of CTCL have been the target of intense study, increasing the knowledge of CTCL genomic alterations, discovering novel biomarkers, and potential targets for patient-specific therapy. However, the detailed pathogenesis of CTCL develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 96 publications
(138 reference statements)
0
10
0
1
Order By: Relevance
“…Genes with potentially prognostic value were identified [9,11], but results emphasize the need for personalized precision medicine [10,12]. Moreover, skin barrier dysfunction and upregulated virus entry pathways [12] may reflect increased susceptibility for skin infections already clinically observed in CTCL patients [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes with potentially prognostic value were identified [9,11], but results emphasize the need for personalized precision medicine [10,12]. Moreover, skin barrier dysfunction and upregulated virus entry pathways [12] may reflect increased susceptibility for skin infections already clinically observed in CTCL patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…These challenges underline the need for better diagnostic and prognostic tools [8]. The variable nature of CTCL comes in hand with strong transcriptome heterogeneity (inter-patient and intra-tumoural) on both the bulk [9] and the single-cell level [10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of immune evasion-related gene alterations leading to abnormal expression of PD1, PD-L1 and PD-L2 and co-stimulatory elements such as CD28-ICOS have also impulse the investigation of anti-PD1/PD-L1 antibodies for MF and SS patient treatment 230 . In addition, the high clonal heterogeneity detected in the tumor populations, targeting the microenvironment is being considered as an alternative therapeutic opportunity in MF and other CTCL 221,231 OTHER CTCL DISTINCT FROM MF AND SS Additional clinical variants of CTCL have been recognized in the WHO classification that include the indolent primary cutaneous CD30 (+) lymphoproliferative disorders (LPD) and the more aggressive cytotoxic CTCL subtypes: extranodal natural killer T-cell lymphoma; primary cutaneous gamma-delta Tcell lymphoma; primary cutaneous CD8(+) aggressive epidermotropic lymphoma (pcAETCL) and the subcutaneous panniculitis-like T-cell lymphoma (SPTCL) 65,232 .…”
Section: Genetic and Epigenetics Insightsmentioning
confidence: 99%
“…These effects on the pathogenesis of CTCL have been reported in many preclinical studies ( 57 ). In addition, the mechanisms of HDACi resistance in terms of the heterogeneity of advanced MF/SS have been investigated ( 58 ).…”
Section: Histone Modification In Ctclmentioning
confidence: 99%
“…The low overall response rate (approximately 30–40%) of HDACis in CTCL is probably related to HDACi resistance in malignant T cells. Cytogenetic and genomic studies have recently provided data on the molecular mechanism for apoptosis resistance in CTCL malignant T cells and data on the molecular heterogeneity of CTCL cell populations ( Figure 2 ) ( 58 ). In one study, STAT3 and RAD23B genotypes were reported to influence primary HDACi sensitivity in Sézary cells ( 64 ).…”
Section: Histone Modification In Ctclmentioning
confidence: 99%